2016
DOI: 10.1128/aem.00829-16
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Shiga Toxin-Producing Escherichia coli Shedding by Dairy and Beef Cattle

Abstract: Shiga toxin-producing Escherichia coli (STEC) is an important foodborne pathogen that can cause hemorrhagic colitis and hemolytic-uremic syndrome. Cattle are the primary reservoir for STEC, and food or water contaminated with cattle feces is the most common source of infections in humans. Consequently, we conducted a cross-sectional study of 1,096 cattle in six dairy herds (n ‫؍‬ 718 animals) and five beef herds (n ‫؍‬ 378 animals) in the summers of 2011 and 2012 to identify epidemiological factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 45 publications
(58 reference statements)
4
52
1
Order By: Relevance
“…In this study, high temperature and rain were found to be associated with STEC prevalence. Similarly, a previous study reported higher STEC prevalence in hot seasons than in cold seasons [3133]. In addition, rainfall has been considered an important transmission factor for STEC.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, high temperature and rain were found to be associated with STEC prevalence. Similarly, a previous study reported higher STEC prevalence in hot seasons than in cold seasons [3133]. In addition, rainfall has been considered an important transmission factor for STEC.…”
Section: Discussionmentioning
confidence: 78%
“…Prevalence ranges from 4% to 83% in feedlot cattle (Fegan et al 2004, Arthur et al 2009, Venegas-Vargas et al 2016). This marked difference in prevalence is likely due to a number of dynamic risk factors, including environment (Stanford et al 2016), animal age (Mir et al 2015), diet (Venegas-Vargas et al 2016), season (Stanford et al 2016), and year (Venegas-Vargas et al 2016). Contrary to STEC prevalence in cattle, the prevalence of STEC in wild birds is consistently lower.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli O157:H7 is a human pathogen that belongs to the Shiga toxin-producing E. coli or STEC group, an autonomous and serologically diverse group of bacteria that carry Shiga toxin-encoding genes on bacteriophages (Beutin et al 2004;Venegas-Vargas et al 2016). These strains synthesize Shiga toxin 1 (Stx1), Shiga toxin 2 (Stx2) or both (Obrig et al 2003;Rahal et al 2012), and additional toxin subtypes have also been described (Scheutz et al 2012).…”
Section: Insights Into Virulencementioning
confidence: 99%
“…In a study conducted in dairy cattle from Michigan farms, STEC shedding increased 2.5-fold when the average temperature during the 1-to 5-day period preceding sample collection exceeded 28.9 • C (Venegas-Vargas et al 2016). Cattle lactating for the first time had a 1.8-fold higher risk to shed STEC as compared to animals that have lactated at least twice, and animals that had been producing milk for less than 31 days had a 3.9-fold higher risk to shed the bacteria as compared to animals that had been producing milk for 31 days or longer (Venegas-Vargas et al 2016).…”
Section: Environmental Factors Involved In Super-sheddingmentioning
confidence: 99%